Merleau-Ponty and the Digital Era: Flesh, Hybridization, and Posthuman - Ferro, Floriana (Scenari, 2021)
The paper discusses a posthuman reading of Merleau-Ponty’s later works and an application of the concept of flesh to the digital dimension. Whereas, in the Phenomenology of Perception, the world and other beings are seen from an egological and human perspective, in The Visible and the Invisible this perspective is reshaped. Human body is made of the same stuff of other bodies, and they constitute a common being, the flesh of the world. Merleau-Ponty sets out a path through flat ontology and posthumanism, opposing human perspective as a privileged one. His posthuman turn passes through the concepts of reversibility and divergence. Humans are made of the same stuff as non-humans, so they reverse into one another, but, on the other hand, they are not reduced to an undifferentiated entity, because of their divergence. Merleau-Ponty’s problematizing perspective is here actualized and applied to the hybridization between human bodies and digital protheses.